Spiritual Foundations of Islamic Educational Leadership: Revisiting Al-Ghazali, Ibn Taymiyyah, and Syed Naquib al-Attas - Benny Prasetiya; Heri Rifhan halili (Al-Hikmah: International Journal of Islamic Studies, 2025)
This article explores the concept of religiosity in Islamic educational leadership through a comparative analysis of the thought of three prominent scholars: Al-Ghazali, Ibn Taymiyyah, and Syed Muhammad Naquib al-Attas. Employing a library research approach and content analysis method, the study examines how each thinker formulates the relationship between divine values, knowledge, and leadership responsibility within the context of education. The findings reveal a shared emphasis on the necessity of a spiritual foundation in leadership, yet each adopts a different approach: Al-Ghazali foregrounds the spiritual-ethical dimension through tazkiyat al-nafs (purification of the soul); Ibn Taymiyyah underscores a legalistic approach and the principle of amar ma’ruf nahi munkar (enjoining good and forbidding evil); while al-Attas highlights the cosmological and adabic dimension within the framework of the Islamisation of knowledge. The study proposes a conceptual typology of religiosity-based leadership through three distinctive models that have rarely been integrated in previous Islamic leadership literature. These findings have implications for the development of an integrative, contextual, and transformative paradigm of Islamic educational leadership, particularly relevant in addressing the contemporary global crisis of values in education